Orthopaedic physicians’ awareness, diagnostic challenges and referral barriers in axial spondyloarthritis: insights from a nationwide survey in Germany - Proft, Fabian; Moissl-Blanke, Angela P.; Kirsten, Natalia; Pfeil, Alexander; Simon, David; Bibi, Igor; Olsavszky, Victor; Fleyder, Anastasia; Otten, Marina; Pachowsky, Milena; Leipe, Jan (Therapeutic advances in musculoskeletal disease, 2025)
Background: Axial spondyloarthritis (axSpA) is a chronic inflammatory disease primarily affecting the spine and sacroiliac joints, potentially leading to pain, stiffness and disability. Despite diagnostic advances, delays persist. Orthopaedic physicians, often the first specialists consulted for back pain, play a crucial role in early detection and referral to rheumatologists. - Objectives: To evaluate orthopaedic physicians’ awareness and management of axSpA and factors that might affect appropriate management. - Design: An online nationwide survey was conducted among orthopaedic physicians in Germany to assess their axSpA knowledge, diagnostic and therapeutic practices and referral behaviours. - Methods: Descriptive statistics were used to summarize participant characteristics and management practices. Machine learning and subgroup analyses identified factors influencing clinical practices. - Results: Among 103 orthopaedic physicians (mean age 49.2 ± 11.4 years; 46.6% female), 48.5% practised in both conservative and surgical settings, and 20% held additional qualifications in orthopaedic rheumatology. While 92% regularly treated chronic back pain, only 11.0% estimated the prevalence of inflammatory back pain (IBP) at ⩾5%. Human leucocyte antigen (HLA)-B27 testing was always used by 17.5%, magnetic resonance imaging (MRI) by 14.6% and IBP classification criteria by 22.5%. Nonsteroidal anti-inflammatory drugs were the most common treatment (77%), while 72.1% never used biological disease-modifying antirheumatic drugs. Digital health applications were rarely recommended (14.6%). The majority of physicians (63%) directly referred suspected axSpA cases to rheumatologists, 29% collaborated with rheumatologists and 12% managed cases independently. Referral barriers included long waiting times (66%) and limited appointment availability (33%), while timely appointments (59%) and better referral knowledge (58%) facilitated referrals. Higher self-reported axSpA knowledge was associated with attending ⩾2 rheumatology seminars, conservative orthopaedics settings, regular HLA-B27 testing and familiarity with axSpA MRI results. - Conclusion: This study reveals substantial opportunities to improve axSpA awareness, management and referrals among orthopaedic physicians. Targeted education and streamlined referral systems, including easier access to rheumatology appointments, could enable earlier diagnosis and better axSpA management.